2021
DOI: 10.3390/su13041723
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Symbiosis: A Sectoral Analysis on Enablers and Barriers

Abstract: Industrial Symbiosis (IS) around the world in the last 20 years had been characterized through an extensive analysis of scientific papers on the IS emerging process, with a special focus on its early stages. The literature suggests that in this process there are key factors (enablers, barriers, triggers, and challenges) that play a critical role in Industrial Symbiosis. From those factors, the enablers and barriers have been highlighted in most of the studies in their different dimensions (social, economic, po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 82 publications
0
24
0
1
Order By: Relevance
“…Promoting inclusive and sustainable industrialization (target 9.2) has demonstrated the potential of IS in creating new businesses and jobs [8]. Upgrade infrastructure (target 9.4) to implement industrial symbiosis can benefit all parties involved and contribute significantly to sustainable growth and greenhouse gas reduction (GHG), especially in energy-intensive sectors such as the cement sector [32]. Regarding the enhanced scientific research (target 9.5), several studies point out that in order to achieve an effective implementation of the industrial symbiosis it is fundamental to promote research in industry, designed to solve real-world problems and generate insights with direct high utility for business practices [33].…”
Section: Resultsmentioning
confidence: 99%
“…Promoting inclusive and sustainable industrialization (target 9.2) has demonstrated the potential of IS in creating new businesses and jobs [8]. Upgrade infrastructure (target 9.4) to implement industrial symbiosis can benefit all parties involved and contribute significantly to sustainable growth and greenhouse gas reduction (GHG), especially in energy-intensive sectors such as the cement sector [32]. Regarding the enhanced scientific research (target 9.5), several studies point out that in order to achieve an effective implementation of the industrial symbiosis it is fundamental to promote research in industry, designed to solve real-world problems and generate insights with direct high utility for business practices [33].…”
Section: Resultsmentioning
confidence: 99%
“…Especially related to policy, there are typically regulatory barriers to trading waste and, even if it is possible, this is often blocked by hard to acquire permits, and there is uncertainty about future policies [77]. Other relevant barriers identified by Henriques et al (2021) [77] are an instable demand for circular products, a lack of financing (both private and public), and a lack of knowledge on available solutions, complemented by a lack of intermediaries that enable communication and set up networks for innovation. In the case of using recycled products, governments can take away barriers by sharing information, settings standards, preferring recycled products in green public procurement, and by stimulating the market [78].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…These studies have also recognized the existence of a group of factors that appear and end up being crucial for the synergies promotion [12,41], they are normally called key or intervening factors. Those factors are defined as determinants for the emerging process of synergies [42], cross-cutting different dimensions, namely, policy, social, economic, intermediaries, geographical, and technological [4,12,40,[42][43][44][45][46][47][48]. Over the years, literature categorizes these key factors into different groups: enablers, drivers, challenges, barriers, etc.…”
Section: Industrial Symbiosis and Its Emerging Processmentioning
confidence: 99%
“…The internal common risk factors listed in the first cluster are mostly associated with financial risks such as dependency and lack of funds to promote IS [39,44,80]. Social factors such as lack of motivation [47] and lack of knowledge [42] were also identified. From an external perspective, lack of policy that allows symbiotic exchanges [31,38], the complexity of the regulations for waste recovery, and limitations of national financing in terms of industrial sustainability were the main risk factors identified.…”
Section: Assessing Implementation Riskmentioning
confidence: 99%
See 1 more Smart Citation